2018
DOI: 10.1029/2018gl080976
|View full text |Cite
|
Sign up to set email alerts
|

Lake Level and Surface Topography Measured With Spaceborne GNSS‐Reflectometry From CYGNSS Mission: Example for the Lake Qinghai

Abstract: This paper demonstrates inland water altimetry of spaceborne Global Navigation Satellite System‐Reflectometry (GNSS‐R) using the Cyclone GNSS (CYGNSS) mission data. From 12 tracks of raw data overpassing the Lake Qinghai, the bistatic group delay and carrier phase delay are extracted from the quasi‐specular GNSS reflections. The water levels derived from the group delay observations are consistent with the Cryosat‐2 and in situ gauge measurements. The surface topography profiles from the phase delay measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…However, in Marine GNSS reflection measurement, the power waveform and peak are essentially determined by the roughness. Therefore, this method can be used in Global Navigation Satellite System-Reflectometry (GNSS-R) altimetry if the surface is smooth enough [21].…”
Section: Tracking Point Delay Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Marine GNSS reflection measurement, the power waveform and peak are essentially determined by the roughness. Therefore, this method can be used in Global Navigation Satellite System-Reflectometry (GNSS-R) altimetry if the surface is smooth enough [21].…”
Section: Tracking Point Delay Estimation Methodsmentioning
confidence: 99%
“…After matching, a series of corresponding lon 0 , lat 0 , H measured , and H model can be evaluated. In this paper, the bias average absolute error (MAE), root mean square error (RMSE), and correlation coefficient (R) are calculated by using Formulas (20)(21)(22)(23).…”
Section: Mssh From Cygnssmentioning
confidence: 99%
“…The GNSS-R technique can be utilized to retrieve geophysical parameters such as sea surface height [1,2], ocean surface wind [3,4], vegetation [5,6], and soil moisture [7,8], mainly based on delay-Doppler maps (DDMs). It was noted that several studies have been conducted on GNSS-R with phase observation (i.e., carrier phase measurement) [9][10][11][12], which is not included in DDMs and is not discussed in this paper. To generate a DDM, the GNSS-R receiver performs a series of correlation processing procedures at different code phase delays and Doppler frequency bins.…”
Section: Introductionmentioning
confidence: 99%
“…CYGNSS is a constellation consisting of eight small satellites carrying GNSS receivers specially designed to capture surface-reflected GNSS signals over the tropics to retrieve ocean surface wind speeds. To explore additional capabilities, previous studies have shown initial applications to monitor land surface hydrological components such as soil moisture [7,8], lake ice thickness/water levels [9,10], and wetlands [11]. The first attempt, described in [6], used CYGNSS data to map flood inundation during the 2017 Atlantic hurricane season.…”
Section: Introductionmentioning
confidence: 99%